Pengaruh Metode Drill Menggunakan Quizizz Terhadap Peningkatan Kemampuan Menghafal Huruf Hiragana Siswa Kelas X SMA Negeri 1 Batu - Rosalina Abhi Pawestri; Febi Ariani Saragih (Universitas Negeri Surabaya, 2021)
This study aims to discover the effect, the learning process carried out by the teacher, and students' perceptions in the application of the drill method using quizizz to improve students' ability in memorizing hiragana letters. The researcher used the theory of drill method and discuss the steps while observing the learning process of hiragana. This research is pre-experimental research uses a quantitative approach method with a pre-experimental one-group pretest-posttest design. The data was collected through tests, observations, closed-ended questionnaires, and documentation. In processing and analyzing the data, the researcher used the assistance of the Statistical Package for the Social Sciences (SPSS) version 21 program to drawing a conclusion using descriptive statistics. The results show that the average score for the pretest was 58.8 and 83.6 for the posttest score. From the test results using Paired Sample t-test, t count is greater than t table (t count = 7,698 > t table = 2,026) with a significance value of 0.000. The conclusion is the drill method using Quizziz could significantly improve students' ability to memorize hiragana letters. How well the teacher applied the method also affects the results. In addition, based on the results of the questionnaire, the students show a good perception toward the use of drill method through Quizizz to improve their ability in memorizing hiragana letters. Keywords: Drill Method, Memorization Skills, Hiragana